Impementasi Algoritma Naive Bayes Terhadap Analisis Sentimen Opini Masyarakat Indonesia Mengenai Drama Korea Pada Twitter - Resti Amelia; Darmansah Darmansah; Nanda Sesty Prastiwi; Muhammad Eka Purbaya (JURIKOM (Jurnal Riset Komputer), 2022)
Korean culture in the last two decades has shaken the whole world, including Indonesia, almost all millennial children talk about Korean culture, whether from dramas, films, songs, fashion, lifestyle, industrial products have begun to penetrate the lives of Indonesian people. One of the trends of public interest is Korean film drama. However, in the expansion of Korean film dramas in Indonesia, there must still be a negative perspective, so an analysis of the sentiments of Indonesian people's opinions regarding Korean culture is currently on the rise. This sentiment analysis data is taken from comments about Korean dramas that are widely written on Twitter. From the many opinions about Korean dramas, a classification is needed according to the existing sentiments so that it will be easy to get the tendency of opinions written on Twitter towards Korean dramas whether they tend to have positive, neutral or negative opinions. In the analysis of opinion sentiment using a Naive Bayes approach taken from Twitter Social Media. The application of the Nave Bayes algorithm in grouping positive, neutral and negative sentiments based on Korean drama commentary review data collected. The purpose of this study is to analyze public opinion and sentiment on Korean dramas on Twitter based on 100 data taken, using Orange tools for the sentiment analysis process. The results given show a percentage value of 69% by calculating the Naive Bayes algorithm